Гиперлипидемическое и продисбиотическое действие сливочного масла - Левицкий, А.П.; Левченко, Е.М.; Квасницкая, О.Б. (Актуальні проблеми транспортної медицини, 2014)
Потребление крысами высокожирового рациона (ВЖР), содержащего 15 %
сливочного масла, вызывает развитие гиперлипидемии (увеличение содержания
в сыворотке крови триглицеридов и холестерина), тогда как ВЖР с подсолнечным маслом вызывает лишь гиперхолестеринемию, а также увеличение содержания триглицеридов и холестерина в печени. ВЖР со сливочным маслом вызывает
развитие дисбиоза в слизистой тонкой кишки и в печени. Вживанная щурами високожирового раціону (ВЖР), який містить 15
% молочного жиру, викликає розвиток гіперліпідемії (збільшення вмісту в
сироватці крові тригліцеридів і холестерину), в той час як ВЖР з соняшниковою олією викликає лише гіперхолестеринемію, а також збільшення
вмісту в печінці тригліцеридіві холестерину. ВЖР з молочним жиром викликає розвиток дисбіозу в слизовій
оболонці тонкої кишки і в печінці. Aim: Our aim is to determine the
effect of high-fat meal (HFM) containing
15 % butter on the serum and liver lipid
profile, far more on the degree of
dysbiosis in the mucosa of the small
intestine and in the liver.
Materials and Methods: In our
experiments we fed 18 white rats with
HFM containing 15 % butter for 41 days.
In the control group we used HFM
containing 15 % sunflower oil.
Triglyceride (TG) and Cholesterol (Ch)
in the blood serum were detected by
fermentative methods. The degree of
dysbiosis was calculated by the ratio of
relative activities of urease and
lysozyme.
Results: We found that consuming
HFM with butter increases TG and Ch
levels in the blood serum and induces
the development of dysbiosis in the
mucosa of the small intestine and in
the liver.
Conclusions: Butter containing
significant amount of palmitinic acid ha